Sustainable urban farming management: A comparison study in Thailand and Indonesia - Fauzia, Assyifa (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: Urban farming is the process of producing food and other products on urban land that provides social and environmental benefits and reduces negative environmental, social and health impacts associated with urban production and consumption patterns. Findings: This article identifies the key characteristics of urban agriculture in Thailand and Indonesia, focusing on the approaches and administration of production and distribution procedures. Methods: The approach employed in this article involves descriptive analysis, utilizing data sources derived from literature reviews of diverse scientific articles associated with urban farming management in Thailand and Indonesia in the 2015-2023 timeframe and then comparative analysis. Conclusion: Urban farming management in Thailand, especially in the Bangkok Metro Regions (BMR), and in Indonesia, especially in Jakarta, faces various challenges. The BMR in Thailand has been trying to improve food self-sufficiency since 2010, utilizing canals as a source of irrigation and transportation, and has the constraint of the lack of connection of urban agricultural actors to traditional markets. High population density and conversion of agricultural land in Jakarta are serious problems, especially after the 1998 economic crisis, urban agriculture developed with residents using land for agriculture, but uncertainty over land rights increased due to industrialization. A challenge in urban agriculture management in Thailand and Indonesia is the lack of coordination in urban agriculture regulations and infrastructure and stakeholders can address this through better communication between urban agricultural actors, retailers, and non-farming households.